Guided self-management targeting anxiety and activity participation in older Veterans. (3rd October 2021) - Gould, Christine E.; Carlson, Chalise; Wetherell, Julie Loebach; O'Hara, Ruth; Goldstein, Mary K.; Loup, Julia R.; Ma, Flora; Beaudreau, Sherry A.
Abstract: Objectives: This study examined the acceptance, feasibility, and preliminary effects of a guided self-management intervention using video delivery and a telephone coach on anxiety and activity engagement. Method: Ten Veterans aged 60 years or older with anxiety disorders determined by Structured Clinical Interview for Diagnostic and Statistical Manual 5 th edition (SCID-5) at baseline visit participated in this non-randomized study examining a 4-week guided self-management intervention for anxiety. Feasibility was examined using participation engagement with the intervention. Measures of anxiety (Geriatric Anxiety Scale, PROMIS Anxiety Scale, Anxiety Control Questionnaire), depression (Patient Health Questionnaire 9-item), and activity participation (modified Activity Card Sort) administered at baseline and final (week 8) visit provided estimates of preliminary intervention effects. The Geriatric Anxiety Scale also was administered by phone at week 4. Participants completed a semi-structured qualitative interview at the final visit, which provided information about the acceptability, benefits of intervention, and barriers to engagement. Results: All participants ( N = 10) reported that the intervention somewhat or completely met their expectations, demonstrating intervention acceptability. Intervention completers ( n = 9) experienced reduced anxiety over the first 4 weeks, alongside significant improvements in anxiety control and personalized activity goals across 8 weeks. However, anxiety symptoms tended to return to baseline at follow-up. Participants identified the relaxation videos and promotion of a daily relaxation routine as the most helpful intervention components. Conclusions: Findings indicate that the intervention may improve activity participation and reduce anxiety. Thus, guided self-management interventions show promise for reducing distress and maintaining engagement later in life.